2019
DOI: 10.1016/j.stemcr.2019.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Macroscale Cardiac Constructs Elicit Human Myocardial Tissue-like Functionality

Abstract: Summary In vitro surrogate models of human cardiac tissue hold great promise in disease modeling, cardiotoxicity testing, and future applications in regenerative medicine. However, the generation of engineered human cardiac constructs with tissue-like functionality is currently thwarted by difficulties in achieving efficient maturation at the cellular and/or tissular level. Here, we report on the design and implementation of a platform for the production of engineered cardiac macrotissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…We have investigated spontaneous APs in 2D-cultured hiPSC-CMs, and in cardiac spheroids with and without CF. It has been hypothesized that 3D culture induces a more mature electric phenotype, although in those studies additional interventions were performed such as contractility training or different media formulations (Ronaldson-Bouchard et al, 2018;LaBarge et al, 2019;Valls-Margarit et al, 2019). Resting membrane potential in immature cardiomyocytes has been reported around −60 and −90 mV in adult cells (Barbuti et al, 2016;Zhao et al, 2018), which is in agreement with our results in monolayer-cultured hiPSC-CMs.…”
Section: Electrical and Contractile Functionsupporting
confidence: 90%
“…We have investigated spontaneous APs in 2D-cultured hiPSC-CMs, and in cardiac spheroids with and without CF. It has been hypothesized that 3D culture induces a more mature electric phenotype, although in those studies additional interventions were performed such as contractility training or different media formulations (Ronaldson-Bouchard et al, 2018;LaBarge et al, 2019;Valls-Margarit et al, 2019). Resting membrane potential in immature cardiomyocytes has been reported around −60 and −90 mV in adult cells (Barbuti et al, 2016;Zhao et al, 2018), which is in agreement with our results in monolayer-cultured hiPSC-CMs.…”
Section: Electrical and Contractile Functionsupporting
confidence: 90%
“…Previous studies have shown the formation of a functional syncytium in 2D cultures mainly due to hypertrophic growth of hiPSC-CMs (Kumar et al, 2019). On the contrary, functional coupling between cardiomyocytes cultured on 3D constructs has been reported only after mechanical or electrical stimulation (Valls-Margarit et al, 2019). Interestingly, in our study, we observed the formation of a functional syncytium of hiPSC-CMs cultured on the coaxial patches, evidenced by the expression of the gap junction protein, Cx-43, and synchronous calcium transients across the patch.…”
Section: Discussionmentioning
confidence: 98%
“…Although 3D cultures of hiPSC-CMs have great potential to make more matured cardiomyocytes, it is insufficient to do so by itself, and a combination of the above-mentioned maturationpromoting methods worked in 2D must be utilized within a 3D setting, which includes cell-cell interaction (e.g., fibroblasts) (Zhang et al, 2017;King et al, 2019;Valls-Margarit et al, 2019;Yan et al, 2019), hormones (Balistreri et al, 2017;Huang et al, 2020), and electrical and physiological stimulation. Below, we will provide a brief review of the electrical and physiological stimulation applied to 3D cultures to reach the ultimate goal.…”
Section: Enhancing Hipsc-cms Maturation In 3d Culture Systemsmentioning
confidence: 99%